Polianthes venustuliflora (Asparagaceae, Agavoideae), a new endemic species of Michoacán, Mexico - Solano Camacho, Eloy; García Mendoza, Abisaí Josué; Ríos-Gómez, Ramiro (Instituto de Ecología, A.C., 2018)
Background and Aims: Polianthes is an endemic genus from Mexico, which consists of 19 species, including the one described here. As part of a systematic review of the genus, a botanical exploration was carried out throughout its geographical range where several new species were discovered. Some of these have already been described and published. We here will describe and illustrate P. venustuliflora, endemic to the state of Michoacán, which differs morphologically from P. montana and P. platyphylla.Methods: As part of the research process we have reviewed specimens of Polianthes collected in the north of the state of Michoacán, from different national herbarium collections and two foreign herbaria. These individuals have morphological characteristics that differ from those of the species already described. In addition, a botanical exploration was carried out in the area to prepare herbarium specimens in which vegetative and reproductive characteristics were also evaluated, allowing to morphologically separate Polianthes venustuliflora from similar species. The risk category was evaluated according to the method proposed by the International Union for Conservation of Nature.Key results: Polianthes venustuliflora is described and illustrated as a new species from the state of Michoacán, Mexico. This new species is morphologically related to P. montana and P. platyphylla, differing from these by presenting 3 to 7 leaves in the rosette, occasionally 9, leaves from 12 to 35, rarely 40 cm in length, with papillose to regularly denticulated margin; length of the inflorescence from 24 to 68 cm and number of floral nodes from 3 to 7. It is assigned the category of risk in Critically Endangered (CR).Conclusions: Polianthes venustuliflora is endemic to the north of Michoacán. According to criterion B of the IUCN, it is considered a Critically Endangered species (CR).